Knowledge, Awareness and Practice of Oral Motor Exercises among Speech and Language Therapists/Pathologists in Various Disorders - Rija Aziz Malik, Amna Rashid, Muhammad Sikander Ghayas Khan, Muhammad Ahmed, Muhammad Azzam Khan, Arslan Saleem Chugtai, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Oral motor exercises are widely used for treatment of speech disorders by the speech and language pathologists worldwide. Oral motor exercises are oral activities that impact speech production without actually producing speech. These activities include lateral tongue movements, crumpling of lips, panting of cheeks, breathing out and swallowing. Speech and language pathologists in many countries carry on with the use oral motor exercises for treatment of various speech disorders in their therapy sessions. Objective: This study was designed to investigate the knowledge, awareness and practice of oral motor exercises among speech and language pathologists in various disorders. Methodology: A standardized questionnaire from the article “The use of oral motor exercises among Indian speech and language pathologists to treat speech disorders” was taken by permission of author. The questionnaire future betrothed to extract information regarding the use of oral motor exercises. 207 participants were addressed. Participants were Pakistani speech and language pathologists. The questionnaire contains three sections. First section consists of demographic information, second and third sections extract information from the pathologists who did and did not choose to use oral motor exercises, respectively. A written consent was taken from the pathologists to participate in this research work and then questionnaire was given to fill. Descriptive statistics were implemented to analyze answers. Observational cross-sectional study was used and data was gathered from SLPs at University of Lahore. Results: Ninety-one (91%) of the speech and language pathologists who responded to the questionnaire demonstrates that they use oral motor exercises to treat speech disorders. Conclusion: The results tells that the percentage of speech and language pathologists preferring to use oral motor exercises is same as the results of other studies done in other countries. The Pakistani speech and language pathologists prefer to use oral motor exercises on base of multitude of beliefs. It is very important for speech and language pathologists to use the principles of evidence-based practice while using oral motor exercises to provide high quality clinical care. Keywords: oral motor exercises, treating speech disorders, speech therapy.